The Effect Of Web-Based Academic Information System Use On Student Satisfaction: A Quantitative Study In Islamic Higher Education - Ade Ikbal Pauji; Rosidah Rida; Ralaivao Hanginiaina Emynorane (JoIEM (Journal of Islamic Education Management), 2025)
This study aims to analyze the effect of web-based Academic Information Systems on student satisfaction. The digital transformation in education requires the optimization of academic information systems to improve the efficiency of both academic and non-academic services. However, the implementation of such systems often faces several challenges, including user resistance, limited infrastructure, and suboptimal data quality. This research employed a quantitative approach with a population of 59 active students from the Islamic Education Management Study Program at the Institut Agama Islam Tasikmalaya. A sample of 51 respondents was determined using the Isaac and Michael formula. Data were collected through questionnaires and documentation studies, with the latter serving as secondary data in the form of institutional records to complement and validate the information obtained from respondents, and then analyzed using validity tests, reliability tests, and t-tests with IBM SPSS version 26. The findings indicate that the levels of system usage and student satisfaction fall into the moderate category. The coefficient of determination test resulted in a value of 31.3%, suggesting that the use of the Academic Information System contributes to student satisfaction, while the remaining 68.7% is influenced by other factors. Furthermore, the t-test produced a significance value of 0.000 (< 0.05), indicating that the use of web-based Academic Information Systems has a significant effect on student satisfaction.